Peran ChatGPT dalam Proses Pembelajaran Mahasiswa di Era Digital Antara Inovasi dan Tantangan Etika Akademik - Desta Amalia; Doly Nofiansyah (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The development of Artificial Intelligence (AI) in education has significantly transformed students’ learning processes in the digital era, particularly through the emergence of ChatGPT. This study aims to analyze the role of ChatGPT in student learning processes and examine the opportunities for innovation as well as the challenges related to academic ethics that arise from its use. The method employed is a literature review by analyzing various scientific articles, both national and international journals, and relevant publications concerning the use of ChatGPT in higher education. The findings indicate that ChatGPT plays an important role as a learning support tool, such as assisting in understanding learning materials, generating ideas, accelerating information retrieval, and enhancing students’ independent learning effectiveness. On the other hand, the use of ChatGPT also presents several serious challenges, particularly in academic ethics, including the potential for plagiarism, dependency on technology, and a decline in students’ critical thinking skills. These findings emphasize that the use of ChatGPT in education must be balanced with clear regulations and a strong understanding of academic ethics. Therefore, collaboration among students, lecturers, and educational institutions is required to guide the use of ChatGPT so that it continues to support academic integrity and does not diminish the essence of the learning process itself. Thus, ChatGPT can serve as a beneficial innovation when used wisely and responsibly within higher education environments.